A qualitative analysis of perceived barriers and motivators to physical activity in children from ethnic minority groups and white British children. - Joyce Ene Omenyo Omojor-Oche; Gavin Daniel Tempest; Florentina Hettinga; Nicola McCullogh (PLoS ONE)
Physical inactivity is a problem worldwide despite the well-known health benefits of physical activity participation. Children from ethnic minority groups report some of the lowest levels of physical activity. In trying to address this, the voices and perspectives of children, especially children from ethnic minority groups, are often overlooked. The primary purpose of this study was to identify and compare the perceived barriers and motivators to physical activity of children from ethnic minority groups and white British children in a UK city. A semi-structured interview on physical activity participation was conducted in English with 20 children aged 8-11 years old (9 from a range of different ethnic minority groups and 11 white British children). The data were coded and analysed via inductive thematic analysis using Nvivo-12. A total of three barriers and eight motivators were identified for both groups. The barriers to physical activity participation were structure of sports; inadequate resources; and children's social circle. The motivators were self-autonomy; self-confidence; enjoyment of physical activity; positive mental health and wellbeing; social circle; structure of sports; institutional motivators; and the introduction of more gender-balanced organised sports. Differences between groups were however noted amongst the subthemes, particularly in relation to barriers. For children from ethnic minority groups, barrier subthemes comprised parental barriers and obligations to siblings; lack of gender-balanced team sports; lack of variety of sports and lack of sporting equipment; and negative feedback from teammates. For white British children, barrier subthemes were lack of adequate play time in school and lack of financial resources. Such barriers may underpin differences in physical activity participation and should be considered in intervention design.